Open Issues In Core Collapse Supernova Theory. - Mezzacappa, Anthony (Proceedings from the Institute for Nuclear Theory ;, 2005)
Efforts to uncover the explosion mechanism of core collapse supernovae and to understand all of their associated phenomena have been ongoing for nearly four decades. Despite this, our theoretical understanding of these cosmic events remains limited; two- and three-dimensional modeling of these events is in its infancy. Most of the modeling efforts over the past four decades have, by necessity, been constrained to spherical symmetry, with the first two-dimensional, albeit simplified, models appearing only during the last decade. Simulations to understand the complex interplay between the turbul.